2016
DOI: 10.1177/0194599816641910
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent in Pediatric Otolaryngology

Abstract: Parental recall of benefits and risks associated with common pediatric otolaryngology procedures was poor. This information is important because a low rate of recall may influence parents' perspectives of the procedure and could alter their decision-making processes or expectations. Methods to improve parental recall should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This was a novel finding that could not be determined in our previous study due to the smaller sample size. 10 Hence, although physicians have varied interaction styles and even dispense different content and amount of information when discussing the same surgical procedure, 24 it did not significantly impact parents' level of decisional conflict. The implication may be that health care provider influences, at least in this relatively homogeneous sample of providers, are not as imperative as parents' perceptions of shared decision making when considering decisional conflict as a measure of decision quality.…”
Section: Discussionmentioning
confidence: 99%
“…This was a novel finding that could not be determined in our previous study due to the smaller sample size. 10 Hence, although physicians have varied interaction styles and even dispense different content and amount of information when discussing the same surgical procedure, 24 it did not significantly impact parents' level of decisional conflict. The implication may be that health care provider influences, at least in this relatively homogeneous sample of providers, are not as imperative as parents' perceptions of shared decision making when considering decisional conflict as a measure of decision quality.…”
Section: Discussionmentioning
confidence: 99%
“…We found that parents correctly answered 80% of knowledge scale items on the postconsult survey following clinician discussion of the relevant item. As the knowledge measure was completed immediately postconsultation, it is not surprising that this accuracy is higher than recall rates reported in previous studies when patients were asked to recall surgical risks and benefits weeks after surgical consultations 13‐17 . However, this finding suggests that pediatric surgical consent might be optimally attained shortly following a comprehensive discussion of the risks and benefits, when parents or other decision‐makers may retain most of the information that was discussed.…”
Section: Discussionmentioning
confidence: 80%
“…As the knowledge measure was completed immediately postconsultation, it is not surprising that this accuracy is higher than recall rates reported in previous studies when patients were asked to recall surgical risks and benefits weeks after surgical consultations. [13][14][15][16][17] However, this finding suggests that pediatric surgical consent might be optimally attained shortly following a comprehensive discussion of the risks and benefits, when parents or other decision-makers may retain most of the information that was discussed. Because parents in our study incorrectly answered 20% of knowledge scale items that had been directly addressed during the consultation, multimodal briefs such as informational handouts, pictures, and videos may be useful to clarify misunderstandings during the conversation and support parents' recall over time.…”
Section: Discussionmentioning
confidence: 99%
“…Other research that evaluates parent-centered outcomes in pediatric tonsillectomy focus on outcomes such as disease-specific and health-related quality of life, parental knowledge about otolaryngologic disease and surgical procedures, parental satisfaction with care, and parental surgical decision conflict . Our study complements these previous studies by looking at parental experiences outside of the clinical context.…”
Section: Discussionmentioning
confidence: 85%